All-cause and cause-specific mortality among Black and White North Carolina state prisoners, 1995-2005 - Rosen, David L. (2011)
PURPOSE: We compared mortality rates among state prisoners and other state residents to identify prisoners’ healthcare needs METHODS: We linked North Carolina prison records with state death records for 1995-2005 to estimate all-cause and cause-specific death rates among Black and White male prisoners aged 20-79 years, and used standardized mortality ratios (SMRs) to compare these observed deaths with the expected number based on death rates among state residents RESULTS: The all-cause SMR of Black prisoners was 0.52 (95%CI: 0.48 0.57), with fewer deaths than expected from accidents, homicides, cardiovascular disease and cancer. The all-cause SMR of White prisoners was 1.12 (95%CI: 1.01, 1.25) with fewer deaths than expected for accidents, but more deaths than expected from viral hepatitis, liver disease, cancer, chronic lower respiratory disease, and HIV. CONCLUSIONS: Mortality of Black prisoners was lower than that of Black state residents for both traumatic and chronic causes of death. Mortality of White prisoners was lower than that of White state residents for accidents, but higher for several chronic causes of death. Future studies should investigate the effect of prisoners’ pre-incarceration and in-prison morbidity, the prison environment, and prison healthcare on prisoners’ patterns of mortality.